Análisis de la determinación del valor razonable en los instrumentos financieros en una institución bancaria de la ciudad de Guayaquil - Villalta Cordero, Cristian Eduardo (2019)
The companies and natural persons that perform economic activities within Ecuador are governed by the rules and regulations established by the Superintendency of Companies, Securities and Insurance. This institution, as a financial control entity, with its own autonomy, constantly publishes regulations, issues regulatory updates and carries out periodic review processes for those entities under its control. Financial institutions are governed by the rules and regulations established by the Superintendency of Banks of Ecuador, which is in charge of controlling, regulating and supervising the entities of the financial system, ensuring that laws are complied with.,,,,,,,,,,